Adverse birth outcomes and parental labor market participation after birth - Falk A. C. Voit (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2023)
Numerous articles have looked at the connection between adverse birth outcomes (low birth weight or preterm birth) and an individual's later socioeconomic status. To this day very few studies have been conducted that specifically address how delivery and adverse birth outcomes affect families and the homes where children grow up. In this study, I use data from the German Socioeconomic Panel (SOEP) to research the association between adverse birth outcomes and several parental labor market outcomes following childbirth. The analysis indicates that low birth weight and preterm birth are not associated with most of the considered parental labor market outcomes after birth. Initial disparities prior to childbirth account for a large extent of the negative relationship between adverse birth outcomes and labor market outcomes after birth.
Keywords: I14; J13; D31; 330; Health and Inequality; Children; Labor market outcomes; SOEP